Analisis Komparatif Konsep Jihad Defensif dan Ofensif dalam Islam dengan Prinsip Hukum Humaniter Internasional: Studi Kasus Perlawanan Hamas - Widianti, Anyta; Hasan, Hamzah; Wahid Haddade, Abdul (Mutawasith: Jurnal Hukum Islam, 2025)
This article aims to analyze and compare the two forms of jihad in Islam with the principles of IHL, in order to assess their compatibility and potential disharmony. The concept of jihad in Islam is often misunderstood, especially when associated with armed conflict. In classical Islamic jurisprudence discourse, jihad is divided into two main forms: defensive jihad (difaa'i) and offensive jihad (tulubi). Meanwhile, international humanitarian law (IHL) regulates the legality and limitations in armed conflict, particularly regarding the protection of civilians and non-combatants. The primary data sources in this study are divided into primary data in Islamic studies such as verses of the Qur'an and the Hadith of the Prophet Muhammad regarding jihad and war, and primary data in International Humanitarian Law, namely the 1949 Geneva Conventions and their Additional Protocols. Meanwhile, secondary data was obtained from literature on Islamic studies and International Humanitarian Law, journals, and research related to Jihad and War. Using a normative-comparative approach to primary and secondary legal sources, it was found that defensive jihad is more compatible in principle with IHL, while offensive jihad has the potential to conflict with modern International Humanitarian Law in practice.